DIVERSIDAD DE MICROARTRÓPODOS (ÁCAROS Y COLÉMBOLOS) DE MUSGOS CORTICÍCOLAS EN LA SELVA BAJA DE NICOLÁS BRAVO, QUINTANA ROO. - Várguez-Noh, Wendy P.; Cutz-Pool, Leopoldo Q. (Instituto de Ecología, A.C., 2013)
The diversity of microarthropods (mites and springtails) in corticolous moss was compared in the floodable lowland Nicolás Bravo, Quintana Roo, included six sampling, carried out in dry, rainy and north season of 2011. 28 families of microarthropods from corticolous moss were recorded, among which the Galumnidae (52.36%), Isotomidae (10.45 %) and Scheloribatidae (9.68%) families were the most abundant, making up 72%, further that showed their maximum abundance at rainy season. There was temporal variation in the density of microarthropods (F (2, 27) = 10.62, p<0.05); the highest density was found at rainy season. The highest diversity was recorded between dry and north season. The highest similarity was observed between rainy and north season (71.58%). For the families Isotomidae, Phytoseiidae, Trombididae, Scheloribatidae and Galumnidae there was a positive correlation between moisture from moss and density while the density of Anystidae and Caeculidae was negatively correlated with moss moisture.